2015
DOI: 10.3390/molecules200712209
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Phenolic Acids, Flavonoids and Iridoid Glycosides in Yinhua Kanggan Tablet by UPLC-QqQ-MS/MS

Abstract: A simple, rapid and specific ultra-performance liquid chromatography-triple quadrupole mass spectrometry method was developed for the analysis of 29 bioactive components (10 phenolic acids, 16 flavonoids, and three iridoid glycosides) in Yinhua Kanggan tablet (YHKGT), a herbal prescription used for treating upper respiratory infections, fevers, coughs and pharyngalgia. The separation was successfully achieved using a Waters Cortecs UPLC C18 column (50 × 2.1 mm, 1.6 μm) and gradient elution with water-0.1% form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Lin et al 30 reported that cryptochlorogenic acid and astragalin were two of the basic compounds present in M. oleifera leaf extracts with molecular weights of 355 and 447, respectively, which is consistent with the results of the present study. Cryptochlorogenic acid possesses inhibitory effects against proteases and many other enzymes, including hepatic glucose-6-phosphatase 31 .…”
Section: Lc-ms/ms Analysis Of the M Oleifera Active Compoundssupporting
confidence: 93%
“…Lin et al 30 reported that cryptochlorogenic acid and astragalin were two of the basic compounds present in M. oleifera leaf extracts with molecular weights of 355 and 447, respectively, which is consistent with the results of the present study. Cryptochlorogenic acid possesses inhibitory effects against proteases and many other enzymes, including hepatic glucose-6-phosphatase 31 .…”
Section: Lc-ms/ms Analysis Of the M Oleifera Active Compoundssupporting
confidence: 93%
“…The PDA detection was conducted at 260 nm. Levels of the IGF were quantitated using Empower software version 3.0 (Waters) [ 10 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A. unedo extracts were solubilized in methanol, filtered, and analysed using an HPLC (U-3000, Thermo, Courtaboeuf, France) coupled to an ESI-QTOF mass spectrometer (Maxis II, Bruker, Champs sur Marne, France), as previously described [22] with some modifications as shown below. The chromatographic separation was performed on a C18 column (Acclaim RSLC polar advantage II, 100 × 2.1 mm, 2.2 µm) maintained at a temperature of 35 • C, with a speed of flow of 0.3 mL/min.…”
Section: Liquid Chromatography-electrospray Ionization-quadrupole-timmentioning
confidence: 99%